Devil makes three - Fountain, Ben (Flatiron Books, 2023)
"Haitian president Jean-Bertrand Aristide has been toppled in a violent coup d'état, bringing to power a brutal military dictatorship. With turmoil in the streets and an international embargo threatening to destroy even the country's most powerful players, some are looking to gain an advantage in chaos--and others are just looking to make it through another day. American expat Matt Amaker, forced out of his beachfront scuba shop by a drug-smuggling operation, turns to hunting colonial Spanish treasure off a remote section of Haiti's southern coast. Misha Variel, a Haitian-American scholar, returns to Haiti to care for her aging parents, and soon stumbles onto an arms-trafficking ring masquerading as a U.S.-government humanitarian aid office. Rookie CIA case officer Audrey O'Donnell finds herself managing a grabbag of intelligence assets in an assignment more difficult and more dubious than she could have imagined. All are embroiled in a game of deceit that culminates in a vicious, zero-sum scramble for survival"--